The Role of Periprostatic Adipose Tissue on Prostate Function in Vascular-Related Disorders - Passos, Gabriela Reolon; Ghezzi, Ana Carolina; Antunes, Edson; de Oliveira, Mariana Gonçalves; Mónica, Fabiola Zakia (Frontiers in Pharmacology, 2021)
The lower urinary tract symptoms (LUTS) secondary to benign prostatic hyperplasia (BPH) are highly prevalent worldwide. Clinical and experimental data suggest that the incidence of LUTS-BPH is higher in patients with vascular-related disorders such as in pelvic ischemia, obesity and diabetes as well as in the ageing population. Obesity is an important risk factor that predisposes to glucose intolerance, insulin resistance, dyslipidemia, type 2 diabetes mellitus and cardiovascular disorders. Prospective studies showed that obese men are more likely to develop LUTS-BPH than non-obese men. Yet, men with greater waist circumferences were also at a greater risk of increased prostate volume and prostate-specific antigen than men with lower waist circumference. BPH is characterized by an enlarged prostate and increased smooth muscle tone, thus causing urinary symptoms. Data from experimental studies showed a significant increase in prostate and epididymal adipose tissue weight of obese mice when compared with lean mice. Adipose tissues that are in direct contact with specific organs have gained attention due to their potential paracrine role. The prostate gland is surrounded by periprostatic adipose tissue (PPAT), which is believed to play a paracrine role by releasing growth factors, pro-inflammatory, pro-oxidant, contractile and anti-contractile substances that interfere in prostate reactivity and growth. Therefore, this review is divided into two main parts, one focusing on the role of adipokines in the context of obesity that can lead to LUTS/BPH and the second part focusing on the mediators released from PPAT and the possible pathways that may interfere in the prostate microenvironment.